Analyzing pathogenic variants in mismatch repair genes: personalized prevention strategies for lynch syndrome in Chinese families - Wang, Xiufang; Ni, Haichun; Zhu, Lin; Huang, Hui; Deng, Aiping; Hu, Jifa; Cai, Wei; Li, Juyi (Frontiers in Medicine, 2025)
BackgroundThis study aimed to analyze the pathogenic variants in one family with colorectal cancer and another with endometrial cancer and provide appropriate personalized prevention strategies for carriers of these genetic mutations.MethodsOne proband with colorectal cancer and another with endometrial cancer and their family members were enrolled in this study. Whole-exome sequencing was used to identify pathogenic gene mutations in both families. We compared the structural difference between the wild-type and mutant MSH2 proteins using SWISS-MODEL and PyMOL visualization software.ResultsWe identified one novel mutation (NM_000251.2:c.1486delT:p.L496*) in the MSH2 gene in Family I and a known mutation (NM_001258271.1:c.884 + 4A > G) in the MLH1 gene in Family II. The novel mutation (NM_000251.2:c.1486delT:p.L496*) caused a stop gain mutation, resulting in the absence of amino acids 496–934 in the mutant MSH2 protein. This led to the loss of Domain 5 and alterations in the sequences of Domain 3 and Domain 4 regions, resulting in premature termination of MSH2 protein coding. The known mutation (NM_001258271.1:c.884 + 4A > G) in MLH1 causes the skipping of exon 10, producing a truncated protein and undergoing nonsense-mediated decay based on literature reports. Thus, 5-fluorouracil-based adjuvant chemotherapy is not recommended for patients with lynch syndromeConclusionThe novel stop gain mutant (NM_000251.2:c.1486delT:p.L496*) in MSH2 is deemed pathogenic for LS, and the mutant (NM_001258271.1:c.884 + 4A > G) in MLH1 has been further confirmed to be pathogenic. These findings expand the spectrum of mismatch repair gene variations in the ethnic group Han of China and reaffirm the importance of genetic testing for LS.